World Social Report 2021 - United Nations Department of Economic; Social Affairs (United Nations, 2021)
The World Social Report 2021 points to new directions in which rural development strategies need to be reconsidered. It offers certain strategic principles, programmes of action, and a set of concrete policies that can be combined to devise effective strategies that can help to realize the potential of rural development and achieve the SDGs. WSR 2021 will reexamine the narrow view of rural development and expand the discussion to include the role of development in achieving the wider set of SDGs. In doing the latter, it intends to pay particular attention to the interaction of rural development with SDG 6 (clean water and sanitation), SDG 8 (economic growth and decent work), SDG 9 (infrastructure), SDG 11 (sustainable communities), SDG 13 (climate change), SDG 14 (life below water) and SDG 15 (life on land). The interlinkages of all these Goals suggest that there exist potential synergies between rural development and sustainable efforts in many other directions.